Bis(merocyanine) Hetero‐Folda‐Dimers: Evaluation of Exciton Coupling between Different Types of π‐Stacked Chromphores. Issue 48 (5th August 2019) - Kirchner, Eva; Bialas, David; Würthner, Frank
Abstract: Exciton coupling between different types of chromophores has been rarely investigated. Herein, a systematic study on the exciton coupling between merocyanine chromophores of different conjugation length with varying excited state energies is presented. In this work well‐defined hetero‐dimer stacks were obtained upon folding of bis(merocyanine) dyes in nonpolar solvents. They show distinctly different absorption properties in comparison with the spectra of the single chromophores, revealing a significant coupling between the different chromophores. The simulated absorption spectra obtained from time‐dependent density functional theory (TD‐DFT) calculations are in good agreement with the experimental spectra. Our theoretical analysis based on an extension of Kasha's exciton theory discloses strong coupling between the dyes' transition dipole moments despite of an excited‐state energy difference of 0.60 eV between the chromophores. Abstract : Exciting coupling : Three well‐defined hetero‐dye stacks comprising two chromophores are obtained upon folding of bis(merocyanine) dyes in nonpolar solvents. Theoretical investigations reveal a strong coupling between the dyes' transition dipole moments within the dye stacks leading to significant changes of the absorption properties upon aggregation, which can be rationalized by molecular exciton theory.